Aktivitas Antibakteri Kombinasi Ekstrak Biji Manjakani (Quercus infectoria) Dan Daun Sirih Merah (Piper crocatum) Terhadap Pertumbuhan Bakteri Klebsiella pneumoniae: Antibacterial Activity Combination of Manjakani Seed Extract (Quercus infectoria) and Red Betel Leaf (Piper crocatum) Against the Growth of Klebsiella pneumoniae. - Ashari, Ayu; Harlita, Tiara Dini; Aina, Ganea Qorry (Borneo Journal of Medical Laboratory Technology, 2023)
Potential plants found in Indonesia that can be used for the treatment of urinary tract infections include: Manjakani seeds (Quercus infectoria) and red betel leaves (Piper crocatum). Manjakani seeds are pharmacologically claimed to have biological activities such as anti-inflammatory, antibacterial and antifungal. Red betel leaf has the potential as an antibacterial in the treatment of infectious diseases. The purpose of this study was to determine the antibacterial activity of the combination of manjakani seed extract and red betel leaf in inhibiting the growth of Klebsiella pneumoniae bacteria. The type of research used istrue experiment study with a completely randomized design (CRD) with three factors, namely the type of solvent n-hexane, ethyl acetate, ethanol 96%, ratio (1:1,1:2,2:1) and concentration (75%,100%) with each treatment being repeated twice. This research was conducted in the microbiology laboratory, Labkes, East Kalimantan. The population in this study is the manjakani plant and red betel plant and tested using the agar diffusion technique method Kirby Bauer with positive control (Ciprofloxacin) and negative control (aquadest). Data analysis used is One Way ANOVA and advanced test methods Duncan with a significance level of 0,05. The results obtained showed that there was an effect of antibacterial activity of Manjakani seed extract and red betel leaf on growth K. pneumoniae. The most effective concentration was found in ethanol 96% extract, (2:1 combination of 100% concentration) of 13,97 mm and an effectiveness of 55,74% with a positive control ciprofloxacin 5µg of 25,06 mm. It can be concluded that the combined extract of manjakani seeds and red betel leaves has antibacterial activity against bacteria Klebsiella pneumoniae,but the potential is still low of ciprofloxacin.